TAFSSA District Agrifood Systems Assessment in Nepal 2023: Female - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
TAFSSA (Transforming Agrifood Systems in South Asia) is a CGIAR Regional Integrated Initiative to support actions that improve equitable access to sustainable healthy diets, improve farmers’ livelihoods and resilience, and conserve land, air, and water resources in South Asia. The TAFSSA district agrifood systems assessment aims to provide a reliable, accessible, and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management with gender as a cross-cutting issue in rural areas of Bangladesh, India, and Nepal. It is designed to be a district-level multi-year assessment. Data were collected in March-April 2023 in the Surkhet and Banke districts in Nepal. Three respondents were interviewed per household: a female adult (aged 20+ years) primarily responsible for managing the household, a male adult (aged 20+ years) primarily responsible for agricultural activities, and an adolescent (aged 10-19 years). The assessment also included a community questionnaire, which interviewed a key informant in the district villages. The interviews with female household respondent were conducted using pretested, structured questionnaires. Information was collected on food intake in the past 24 hours, frequency of consumption of foods, food sources, drivers of food choices, exposure to food advertisements and nutrition related messages, household food security, water access, food shopping practices, food aspirations, food consumption outside of the home, household tasks, perceptions of leisure, and household decision-making.